Antibacterial effect of ethanol extract of moringa oleifera seeds against enterococcus faecalis atcc 29212 - Pratiwi, Ririn Dwi; Kuswandari, Sri; Utomo, Rinaldi Budi (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: One of the important stages in endodontic treatment is root canal irrigation. The most widely used irrigant is sodium hypochlorite (NaOCl), but it is toxic to periapical tissue. Irrigant solutions from natural ingredients that have antibacterial potential are needed, one of which is Moringa oleifera seeds. Bacteria that are often found persistent after root canal treatment are Enterococcus faecalis. The purpose of this study was to determine the antibacterial effect of the ethanol extract of M. oleifera seeds at concentrations of 37.5%, 50%, 67.5% and 75% against E. faecalis.Method: Experimental laboratory research with post-test only control group design was carried out with 4 times replication. Antibacterial activity was tested against E. faecalis ATCC 29212 using paper disc diffusion method on Mueller Hinton Agar (MHA) media. The diameter of the inhibition zone formed was measured. Data were analysed by one-way ANOVA followed by LSD.Result: The 2.5% NaOCl group produced the largest inhibition zone of 16.38 ± 0.95 mm, followed by the 75% extract group of 13.51 ± 0.49 mm, and the smallest was the 37.5% extract group of 4.42 ± 0.27 mm. The negative control (DMSO) did not produce an inhibition zone. The increase in the concentration of the ethanolic extract of M. oleifera seeds resulted in significantly better inhibiting the growth of E. faecalis (p<0.05).Conclusion: Ethanol extract of M. oleifera seeds at 37.5%, 50%, 62.5% and 75% had antibacterial effects against E. faecalis, with the 75% had the strongest antibacterial effect compared to other extract concentrations.